Experiment-based Comparative Analysis of Nonlinear Speed Control Methods for Induction Motors - Vo Thanh Ha; Nguyen Tung Lam; Pham Van Tuan; Nguyen Hong Quang (Journal of Engineering and Technological Sciences, 2021)
Field-oriented control (FOC) for induction motors is widely used in industrial applications. By using a fast and accurate torque controller based on a stator current controller it is possible to flexibly implement advanced speed control methods to achieve proper performance both in transient and steady-state states. In this study, a deadbeat controller was used for the current loop. The nonlinear methods used for the outer loop controller were backstepping, flatness-based control, and exact feedback linearization with state derivative. The dynamic responses of these three controls were compared through various experimental results. The advantages and disadvantages of the different control structures were analyzed and evaluated in detail. Based on this evaluation, an appropriate scheme can be specified when deployed in practice.